Voices of the Filipino diaspora: Communication and cultural identity among Overseas Filipino Workers (OFWs) in Stockholm, Sweden - Tamaño, Lexxus Dominic Espiritu; Lopez, Ronn David Manglicmot (Abdul Media Literasi, 2026)
Communication plays a crucial role in sustaining relationships and preserving traditions, particularly for Overseas Filipino Workers (OFWs), who face both cultural displacement and the need for adaptation. In this sense, digital communication has become a vital tool that bridges the distance between their homeland and the host country. However, while existing studies often emphasize the economic contributions and emotional challenges of OFWs, less attention has been given to how communication sustains cultural identity in diaspora contexts such as Sweden. The main objective of this study is to explore how OFWs in Stockholm use communication, particularly digital media, to preserve their Filipino identity while navigating Swedish society. Using a case study research design, four OFWs were recruited through snowball sampling. The participants are Filipino citizens who have an adequate length of stay in Stockholm and consistently use digital tools to communicate with their families in the Philippines. The gathered data were analyzed thematically using ChatGPT, while researchers ensured proper usage throughout the process via email-based interviews. Findings revealed that OFWs maintain their identity through food, language use, cultural celebrations, and community participation, while digital platforms are essential for family connection and emotional expression. Despite these strategies, participants reported challenges, including language barriers, discrimination, and isolation, which necessitated adjustments in communication styles to accommodate intercultural interactions. These insights underscore the dual role of communication as both a coping mechanism and a cultural anchor, underscoring the need for culturally responsive policies and inclusive spaces that foster diaspora resilience and cross-cultural understanding within the context of Swedish society.